2016
DOI: 10.3390/ijms17101679
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Deep Sequencing Characterization of HCV Samples with Equivocal Typing Results Determined with a Commercial Assay

Abstract: Hepatitis C virus (HCV) is classified into seven phylogenetically distinct genotypes, which are further subdivided into related subtypes. Accurate assignment of genotype/subtype is mandatory in the era of directly acting antivirals. Several molecular methods are available for HCV genotyping; however, a relevant number of samples with indeterminate, mixed, or unspecified subtype results, or even with misclassified genotypes, may occur. Using NS5B direct (DS) and ultra-deep pyrosequencing (UDPS), we have tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Interestingly, three of the four patients with subtype-3h had been erroneously identified as harbouring genotype-1 or mixed genotypes. Similarly, of 17 subjects with non-subtyped genotype-1 by Abbott Realtime HCV Genotype II, Minosse et al [20] identified 3 with genotype-3h by NS5B sequencing and ultra-deep pyrosequencing. Moreover, two of our four patients with genotype-3h had Y93H in NS5A, which may affect the second-line DAA regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, three of the four patients with subtype-3h had been erroneously identified as harbouring genotype-1 or mixed genotypes. Similarly, of 17 subjects with non-subtyped genotype-1 by Abbott Realtime HCV Genotype II, Minosse et al [20] identified 3 with genotype-3h by NS5B sequencing and ultra-deep pyrosequencing. Moreover, two of our four patients with genotype-3h had Y93H in NS5A, which may affect the second-line DAA regimen.…”
Section: Discussionmentioning
confidence: 99%
“…However, the true prevalence of this phenomenon remains uncertain and is likely influenced by methodological bias. Although many strategies have been developed for HCV genotyping over time, current HCV genotyping methods may have some limitations in detecting mixed infections [ 41 , 67 , 68 , 69 , 70 ]. Next-generation sequencing techniques provide an alternative to traditional sequencing methods for studying viral genetic diversity.…”
Section: Discussionmentioning
confidence: 99%